OPTICAL AND ELECTRICAL PROPERTIES OF SILICON (Scientific journal of the Fergana State University, 2026)
This article discusses the optical and electrical properties of silicon. General information is provided about silicon as a semiconductor, including light absorption, refractive index, optical transmission, electrical conductivity, carrier mobility, and temperature dependence. Special attention is given to the practical applications of silicon in modern electronics, optoelectronics, solar cells, and photodetectors. The article highlights the scientific and practical significance of the fundamental properties of silicon.